The Role of Diamines in the Formation of Graphene Aerogels - Vrettos, Katerina; Karouta, Niki; Loginos, Panagiotis; Donthula, Suraj; Gournis, Dimitrios; Georgakilas, Vasilios (Frontiers in Materials, 2018)
Aliphatic or aromatic diamines undergo nucleophilic attack on the epoxy groups of graphene oxide under hydrothermal conditions resulting in partial functionalization and partial reduction of the graphenic surface. The overall reaction decreases the solubility of graphene oxide and yields a hydrogel that can be dried to a 3D porous structure classified as an aerogel. This article compares the graphene aerogels derived from different aliphatic and aromatic diamines.